MENINGKATKAN KEMAMPUAN MEMBACA KANJI MELALUI MEDIA FLASHCARD POWER POINT - Dyah Prasetiani (IZUMI, 2013)
Abstract   While learning the kanji, most of the students find difficulties in memorize its yomikata. The problems usually come into their mind when they have to remember lots of kanji along with its meaning and stroke order. Most of the students forget it very soon after they learn it. They have to find effective, fun, and easy learning method to improve their ability in mastering kanji. It could help students consistently review the kanji, especially the jukugo. Flashcard power point could be a good solution to overcome this problem. The result of the study shows that flashcard power point could enhance student’s skill in reading the kanji in a very short time. Key Words: kanji, flashcard